Technology adoption of mobile learning: a study of podcasting. (6th July 2010) - Ho, Chien-Ta Bruce; Chou, Yu-Ting; O'Neill, Peter
Mobile technology has become more mature, which has resulted in the new concept of mobile learning. Combining mobile learning with learning language may make language learning more attractive. Podcasting is one of mobile technology's new applications. This research explores the acceptance and critical factors of applying Podcasting towards learning a language. The design utilises the Unified Theory of Acceptance and Use of Technology (UTAUT) model. We demonstrate that there is a positive attitude towards Podcasting. We also show that performance expectancy is the most important factor when applying Podcasts to learning a language.